An analysis of university students' health information service needs from academic library in the post-COVID-19 age through Kano model. Issue 3 (21st June 2021) - Meng, Yuan; Dong, Li; Guan, Rui; Zhang, Yan
Abstract : Purpose: The study aims to find out the university students' health information service needs in post-COVID-19 age and then consider how to do the health information services well and promote it in further work. Design/methodology/approach: This study uses Kano model to design a questionnaire about university students' health information service needs from academic library and investigates 243 students from seven universities in China. The data generated were analyzed using a statistical tool and presented in tables. Findings: The results show the students' different requirements level of health information services from academic library as must-be requirements, one-dimensional requirements, attractive quality attributes and indifferent quality in post-COVID-19 age. Research limitations/implications: The questionnaire design and the scale of respondents have limitation, such as only focus on Chinese university, have not characteristically research on different group of students. It could optimize to cover more worldwide university students and refer to different groups of students' needs in further research. Originality/value: The paper expands and deepens the theory about university library health information service and provides a practical reference and proposes some suggestions for academic libraries on how to carry out health information services and give the social health institutions inspiration on how to promote the health services, especially in post-COVID-19 age.